Party politics, religion, and women's leadership Lebanon in comparative perspective - Kassem, Fatima Sbaity; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Exploring the interlinkages of political parties, religiosity, and women's leadership and nominations to public office, this book argues that as party religiosity increases, women's chances of assuming leadership positions fall. Combining qualitative and quantitative methods, it advances a new theory of party variation in religiosity.
Keywords: Science; Science; Science, general